The Career Motivation as a Barista (Starbucks Yogyakarta Baristas) - Indra Rahman Sumadijaya; Arif Hartono (International Journal of Economics, Business and Innovation Research, 2025)
Yogyakarta's status as a student there is one industry that benefits from the city's image as a student city: the coffee shop business, in which the cafes that are sprouting across Yogyakarta provide an option for students to do homework or simply hang out and relax with their friends, even became the place for earning more allowance. The findings indicate that the primary reason someone chooses to become a barista is to meet financial demands, get experience, and open up prospects for advancement in their field. This study also demonstrates that for some people, working as a barista is not only a transitory employment, but also part of their professional progression.